Expression of GLUT-1 in oral squamous cell carcinoma in tobacco and non-tobacco users - Neha Azad; Malti Kumari Maurya; Meenakshi Kar; Madhu Mati Goel; Ajay Kumar Singh; Mala Sagar; Divya Mehrotra; Vijay Kumar (Journal of Oral Biology and Craniofacial Research)
Background: GLUTs are a family of proteins that mediate glucose transport through the membrane, expressed in head and neck squamous cell carcinoma. GLUT-1 positivity in malignant cells indicates increased proliferative activity, energy requirements, aggressive behaviour and poor radiation response. Aim: To observe the expression of GLUT-1 protein in oral squamous cell carcinoma in tobacco and non-tobacco users and to correlate the expression with histopathological grading and pathological staging. Methods: 50 cases (25 tobacco and 25 non-tobacco) of oral squamous cell carcinoma, selected during period of August 2014 to July 2015. Histopathological grading, TNM and staging were done. Immunohistochemical staining was performed using standard protocol for paraffin embedded sections. Analysis was performed on SPSS software (Windows version 17.0). Results: Significant association of GLUT-1 expression was found with history of tobacco (p < 0.001), Bryne's grade (p < 0.001), tumour size (p = 0.001), nodal metastasis (p = 0.022) and stage (p < 0.001). Higher GLUT-1 expression in stage II, stage III and stage IV was found as compared to stage I. GLUT-1 immunoexpression also shows progressive switch from membranous to cytoplasmic to combined location correlating with histopathologic grade and pTNM stage. Conclusion: GLUT-1 expression correlates significantly with histological grade and pTNM staging of oral squamous cell carcinoma. It also significantly correlates with tobacco addiction. Thus, GLUT-1 expression may serve as a biomarker for patients of oral squamous cell carcinoma.